STRATEGI PENGEMBANGAN PRODUK PERIKANAN BERDASARKAN INTEGRASI KONSEP BLUE ECONOMY, KEAMANAN PANGAN DAN HALAL - Hana Catur Wahyuni; Puspita Handayani; Rima Azzahra (AGROINTEK, 2023)
Fishery products are one of the potential aquatic resources in Indonesia that have the potential to be developed, considering that Indonesia is rich in aquatic resources. One of the concepts that can be implemented in developing fishery products is the blue economy (BE) concept. This concept is appropriate because it focuses on growth, job creation, and environmentally friendly technological innovation. Meanwhile, food safety and halal are needed to meet the community's need for safe and halal food products. This study aims to identify the factors of strength, weakness, opportunity, threat and develop a strategy for developing fishery products by integrating the concepts of BE, food safety, and halal. on 11 respondents. The research was conducted using the SWOT method through two stages: the first stage to assess internal factors (IF) and external factors (EF). The second stage SO, WO, ST, and WT strategies. The results showed five aspects of strength ten aspects of weakness,  seven aspects of opportunities, and five aspects of threats. The data processing results with IF show that the strength value is 3.59 and the weakness is 3.39. As for the EF value, it is known that the opportunity value is 3.54, and the threat value is 3.58. In the SWOT matrix, it is known that fishery product business actors are in quadrant 2. Furthermore, strategies that can be used in the integration of BE, Food Safety, and Halal by utilizing a digital marketing system, complementing the legality of food safety and halal business actors, product diversification, use of environmentally friendly technology, and integrating BE in food safety and halal policies as well as internal audit instruments